Blinded by the light: Occupant perceptions and visual comfort assessments of three dynamic daylight control systems and shading strategies. (May 2019) - Day, Julia K.; Futrell, Benjamin; Cox, Robert; Ruiz, Shelby N.
Abstract: The introduction of daylight into buildings has great potential to reduce energy use and positively impact building occupants. However, if daylighting designs are poorly conceived, the luminous environment may lead to issues such as glare, headaches, or eye strain. This research presents results from a large-scale study, which included field measurements and surveys of three large commercial office buildings in the U.S. Each building utilized a differing type of shading strategy: automated blinds, electrochromic glazing, and roller shades, respectively. This paper reports findings from the measured physical data and the surveys, which were sent to each building to assess occupants' subjective visual comfort perceptions. In total, 5, 031 surveys were sent to the three buildings, and 1, 068 total occupants responded (a response rate of 21.2%). Key outcomes included the following: (1) occupants who were more pleased with their access to daylight were also more likely to have a higher perceived level of productivity and higher level of satisfaction, (2) occupants' self-reported satisfaction with their workspace significantly differed based on their distance to the window in Buildings 1 and 2, and those closer to the perimeter of the building were more satisfied than those who sat further away from the windows, and (3) the trend of negative responses from occupants in Building 2 (i.e. a perceived gloominess, perpetual sense of an overcast sky, etc.) raise interesting design questions, as related to the use of electrochromic glazing. It is crucial that designers understand daylighting strategies, shading, and corresponding human perceptions of comfort. Highlights: Occupants closer to the perimeter were more satisfied with their workstation. A strong positive correlation between access to daylight and perceived productivity. It is crucial for designers to understand daylighting and perceptions of comfort. An integrated design process may alleviate potential adverse daylight conditions.